Design and Manufacturing of Fixture for Edge Prepration of Elbows - P, Nagasankar; P, Tamilselvi; T V B, Babu; Salahudin S, Jasim; S, Aravindhan; J, Deepak (International Journal of Engineering and Technology, 2018)
This paper is a description of an alternative fixture for the edge preparation of elbows and pipes before welding. The welding will not penetrate the cross section of the pipe if the thickness of the pipes is more than eight millimeter, so edge preparation is done before welding. Fixtures are used to hold the pipes during the process of edge preparation. This paper deals with two major issues from the design of previous fixtures.Requirement of manual handling of the part.Precise rotations are not possible. The fixtures being used currently require more setting up time and they require manual handling to machine the other side. This paper describes a fixture which can reduce manual handling and be able to rotate the elbow either manually or using a motor.
Keywords: Edge preparation; Fixtures; Manual handling; Welding; Manufacturing